Etnobotany Medicinal Plants Tree Group In Traditional Medicine At East Lombok Regency - Lalu Gin Gin Budiarsa; Nurrachman Nurrachman; Sumarjan Sumarjan (Syntax Idea, 2021)
Traditional medicine (Batra) plays a strategic role in society. In addition to working as an alternative treatment, traditional medicine provides an overview of local wisdom found in a community group. This study aims to determine the diversity of species and ethnobotany of medicinal tree group plants by traditional healers in East Lombok Regency. The research method uses descriptive qualitative method. The sampling technique of the respondents was using Puspossive Randome Sampling, while the sampling of plants was using Stratified Sampling. The results of the study include two groups, namely the companion variable consisting of the characteristics of the research area and the characteristics of the research respondents. The characteristics of the area function to determine the development of plants found in agricultural cultivation activities, while the characteristics of the respondents correlate with the species of medicinal trees used. Then in the main variables found 36 species of medicinal plants used by Batra. The tree group plants which were subsequently found mapped the optimal cultivation location in the research area by examining their use to determine the potential for plant development as a commodity in agricultural cultivation